Study of the Effects of SbCl₃ Concentration on Structure, Properties of Mixed Oxide Thin Film Sb₂O₃-SnO₂/HKC and Its Application for the Treatment of Rhodamine B - Huynh, Thu Suong; Bui, Thi Thanh Huyen; La, The Vinh (Old Journal, 2020)
This paper deals with the effects of SbCl₃ concentration on the structure and properties of mixed metal oxide thin film on high alloy steel Cr18Ni12Ti and application for the treatment of Rhodamine B by advanced electrochemical oxidation method. The obtained results of surface morphology (SEM), crystal structure (XRD), cyclic voltammetry (CV), conductivity (four point probers), and absorption spectroscopy (UV-Vis) show that the mixed oxide thin film SnO₂-Sb₂O₃/HKC formed by dipped in a solution containing 10 g/L of SbCl₃, calcined at 450 °C for 5 hours provides the film with the best properties. The formed film has no crack-mud phenomenon, the smallest resistivity and the largest SnO₂ crystal size. The color removal efficiency of Rhodamine B on SnO₂-Sb₂O₃/HKC anode reaches about 95% for 20 minutes of electrolysis time at the current density 12 mA/cm².